An association between residual vein thrombosis and subclinical atherosclerosis: Cross-sectional study. Issue 157 (September 2017) - Prandoni, Paolo; Ciammaichella, Maurizio; Mumoli, Nicola; Zanatta, Nello; Visonà, Adriana; Avruscio, Giampiero; Camporese, Giuseppe; Bucherini, Eugenio; Bova, Carlo; Imberti, Davide; Benedetti, Raffaella; Rossetto, Valeria; et al.
Abstract: Background: The association between venous and arterial thrombotic disorders is still unclear. We assessed the association between residual vein thrombosis (RVT) and subclinical atherosclerosis in a cohort of patients with unprovoked (or associated with weak risk factors) proximal deep-vein thrombosis (DVT). Methods: In a multicenter cross-sectional study, consecutive patients over 40 years free from atherosclerotic disorders received the ultrasound assessment of the leg vein system and that of carotid arteries approximately three months after an episode of proximal DVT. In each center the evaluation was done by two independent assessors. The presence of RVT was defined as the incompressibility of at least 4 mm in either the popliteal or the common femoral vein, and that of subclinical atherosclerosis as the presence of increased (> 0.9 mm) intima-media tickness (IMT) and/or carotid plaques. Results: Out of 252 patients (mean age, 67; males, 53%; unprovoked, 77%), the presence of RVT was found in 139 (55.2%). An increased IMT was shown in 76 (54.7%) patients with and in 35 (31.0%) without RVT (p < 0.001). At least one carotid plaque was found in 80 (57.6%) patients with and in 36 (31.9%) without RVT (p < 0.001). After adjusting for the baseline characteristics, the odds ratio of subclinical atherosclerosis (increased IMT and/or carotid plaques) was 2.8 (95% CI, 1.6 to 4.7). Conclusion: The ultrasound detection of RVT after an episode of proximal DVT that is either unprovoked or triggered by weak risk factors is associated with a higher prevalence of subclinical atherosclerosis. These findings may have implications for patient prognosis. Highlights: There is an important association between venous and arterial thrombotic disorders. Residual vein thrombosis after a DVT episode is associated with a high prevalence of subclinical atherosclerosis. The assessment of residual vein thrombosis may have implications for the management of patients with DVT.